2006
DOI: 10.1016/j.febslet.2006.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic and eukaryotic monothiol glutaredoxins are able to perform the functions of Grx5 in the biogenesis of Fe/S clusters in yeast mitochondria

Abstract: The Saccharomyces cerevisiae monothiol glutaredoxin Grx5 participates in the mitochondrial biogenesis of iron-sulfur clusters. Grx5 homologues exist in organisms from bacteria to humans. Chicken (cGRX5) and human (hGRX5) homologues contain a mitochondrial targeting sequence, suggesting a mitochondrial localization for these two proteins. We have compartmentalized the Escherichia coli and Synechocystis sp. homologues, and also cGRX5 and hGRX5, in the mitochondrial matrix of a yeast grx5 mutant. All four heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 33 publications
(65 reference statements)
1
61
1
Order By: Relevance
“…S5). This result was unexpected given the functional interchangeability among CGFS type Grxs (8,17,18). Interestingly, the poplar chloroplastic PtGRXS16 appears to target to yeast mitochondria and is functional in yeast suppression assays (25).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…S5). This result was unexpected given the functional interchangeability among CGFS type Grxs (8,17,18). Interestingly, the poplar chloroplastic PtGRXS16 appears to target to yeast mitochondria and is functional in yeast suppression assays (25).…”
Section: Discussionmentioning
confidence: 76%
“…Previous reports suggest that CGFS-type monothiol Grxs bind an iron-sulfur cluster (20,21) and suppress yeast grx5 mutant phenotypes (8). AtGRXS16 purified from Escherichia coli cells displayed a dark-brown color, but the color faded quickly.…”
Section: Atgrxs16 Ntd Blocks Its Grx Domain Activity To Suppress Yeasmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (11,73,87,88). Complementation studies using a yeast mutant defective in mitochondrial Grx5, which is unable to maturate iron-sulfur proteins and accumulates toxic levels of intracellular iron, demonstrated the evolutionary conserved function for 1-CGrxs from different eukaryotic and prokaryotic organisms (11,13,61,87). Intriguingly, respective experiments with the three T. brucei 1-C-Grxs revealed that only 1-C-Grx1 modestly rescued the mutant phenotype (27).…”
Section: Glutaredoxins and Regulation Of The Iron-sulfur Metabolismmentioning
confidence: 96%
“…Instead, the capability to coordinate ISCs appears to be a common feature for 1-C-Grxs (16,40,42,43,54,67,89) with yeast Grx7 being, so far, the only known exception (59,60). The latter feature determines an evolutionary conserved and indispensable role of 1-C-Grxs in the biogenesis and assembly of iron-sulfur proteins (11,61) and other cell-specific regulatory functions such as the (in)activation of nuclear transcription factors (35,62,86).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%